Manufacturing a chimpanzee adenovirus-vectored SARS-CoV-2 vaccine to meet global needs - Joe, CCD; Jiang, J; Linke, T; Li, Y; Fedosyuk, S; Gupta, G; Berg, A; Segireddy, RR; Mainwaring, D; Joshi, A; Cashen, P; Rees, B; et al. (Wiley, 2021)
Manufacturing has been the key factor limiting rollout of vaccination during the COVID-19 pandemic, requiring rapid development and large-scale implementation of novel manufacturing technologies. ChAdOx1 nCoV-19 (AZD1222, Vaxzevria) is an efficacious vaccine against SARS-CoV-2, based upon an adenovirus vector. We describe the development of a process for the production of this vaccine and others based upon the same platform, including novel features to facilitate very large-scale production. We discuss the process economics and the “distributed manufacturing” approach we have taken to provide the vaccine at globally-relevant scale and with international security of supply. Together, these approaches have enabled the largest viral vector manufacturing campaign to date, providing a substantial proportion of global COVID-19 vaccine supply at low cost.